Comparison of three enrichment broths for the isolation of thermotolerant acetic acid bacteria from flowers and fruits - Sudsakda S. (2014)
The effectiveness of three enrichment broths, namely potato medium, seed culture medium and sterile distilled water for the isolation of thermotolerant acetic acid bacteria from flowers and fruits was investigated. The numbers of successful isolation obtained from each medium were nearly the same. Seed culture medium was found to give the highest numbers of successful isolation from flower samples whereas potato medium and sterile distilled water gave higher numbers for the isolation from fruits. However, there were no statistically significant differences between the media tested (α>0.05). © 2007 Academic Journals Inc.